Confrontation of the Magnetically Arrested Disc Scenario with Observations of FR II Sources - Rusinek, Katarzyna; Sikora, Marek (Frontiers in Astronomy and Space Sciences, 2017)
The main aim of our work was to check whether powers of jets in FR II radio galaxies (RGs) and quasars (QSOs) can be reproduced by the Magnetically Arrested Disc (MAD) scenario. Assuming that established in the recent numerical simulations of the MAD scenario the (H/R)^2 dependence of the jet production efficiency is correct, we demonstrate that in order to reproduce the observed jet powers in FR II sources: (i) accretion discs must be geometrically much thicker than the standard ones; (ii) and/or that the jet production is strongly modulated.